Sediment Coarsening in Tidal Flats and Stable Coastline of the Abandoned Southern Yellow River Sub-Delta in Response to Fluvial Sediment Flux Decrease During the Past Decades - Zeng, Lin; Zhan, Chao; Wang, Qing; Liu, Xianbin; Wang, Longsheng; Li, Xueyan; Wang, Xin; Yu, Xiang; Zhang, Jinzhi; Cui, Buli (Frontiers in Marine Science, 2021)
Due to remarkable reduction of sediment supply, the vulnerability of Yellow River deltaic system increased and ecological impacts occurred to some extent. To have a comprehensive and quantitative understanding of the morphological evolution of deltas, surficial sediments of tidal flat along the abandoned southern Yellow River sub-delta and two adjacent coastal units were systematically collected and evaluated by grain-size analysis in the study. The results reveal that surficial sediments of the abandoned southern Yellow River sub-delta have been coarsening significantly since the 1980s, as characterised by a decrease in both the mud content and the clay/mud ratio. In particular, the transition from cohesive to non-cohesive sediment was completed between 2007 and 2013. With a sharp decrease in sediment flux from the Yellow River estuary, the flood currents from the submarine coastal slope carry few fine particles into the tidal zone, whereas the ebb currents with reverse direction remove some fine particles from the tidal flat. This is a major cause of sediment coarsening in the tidal flat. As sediment coarsening, the coastline of the abandoned southern Yellow River sub-delta has remained stable. The significant change in the grain size of the tidal flat surficial sediments may have a profound impact on the future coastal geomorphic evolution.